A Multi-Objectives Mathematical Model For Solving Industrial Hazardous Waste Location-Routing-Problem In Johor Region - Hamdan, Nur Aaina Athira; Jamaian, Siti Suhana (Enhanced Knowledge in Sciences and Technology, 2021)
Industrial hazardous waste management that may poses risk to surroundings are including collection and transportation of those waste, treatment, recycling and disposal. This research aims to determine the Pareto optimal of multiple objective function by implementing the Weighted Sum Method and to propose a new strategic treatment with technologies; chemical and incineration, recycling and disposal centres for location-routing problem in Johor region. Two objective function are considered which are minimizing the total cost of transportation, including the total cost of transportation of hazardous materials and waste residues and the fixed cost of opening new treatment, disposal and recycling centres and minimizing the risk exposure of transportation due to population exposure along hazardous material and waste residue transportation routes. The outcomes of the problem solved show a conflict between the two objectives. The cost value can therefore be minimized by slightly increasing the transportation risk value and vice versa. For combination two objectives function into one objective function, a Weighted Sum Method is used with the assist of CPLEX solver is being used to deal with the problem. The potential centres are studied in the Johor region of Malaysia by utilizing Arcmap GIS software which the high population in industrial area of 8 district are considered. The Pareto optimal solution for HAZMAT management problem is identified where the solution shows all the points of non-dominated solution are Pareto optimal solution. Besides, the Pareto optimality for this research is obtained which is an Euclidean distance. The suggested location for opening new industrial hazardous waste management centres are three treatment centres, three recycling centres and two disposal centres.